Hashimoto’s encephalopathy presenting with manic and psychotic features in a 13-year-old girl: a case report - Albdah, Ayman; AlQahtani, Reem; Alamri, Abaad; Alkhudairy, Faris A.; Alsaman, Majd (Frontiers in Psychiatry, 2026)
Hashimoto’s encephalopathy (HE), also known as steroid-responsive encephalopathy associated with autoimmune thyroiditis (SREAT), is a rare autoimmune neuropsychiatric syndrome with highly variable clinical manifestations. Pediatric cases are particularly underrecognized, contributing to diagnostic delays. We describe a 13-year-old female patient who developed subacute behavioral changes, including withdrawal, emotional lability, and progressive manic and psychotic symptoms, over 1 month. Laboratory evaluation showed markedly elevated antithyroid antibodies with normal thyroid hormone levels, and thyroid ultrasound revealed features consistent with autoimmune thyroiditis. Neuroimaging and cerebrospinal fluid studies were unremarkable. The patient demonstrated rapid and sustained improvement following pulse corticosteroids, intravenous immunoglobulin (IVIG), and low-dose antipsychotics. Her clinical course, combined with serological and imaging findings, supported the diagnosis of HE presenting with manic and psychotic features. This case emphasizes the importance of considering HE in the differential diagnosis of acute and subacute onset psychiatric symptoms in children and highlights the diagnostic utility of thyroid antibody testing in such presentations. Categories: Pediatrics; Psychiatry; Neurology; Endocrinology; Immunology